Ecthyma Gangrenosum: A Rare Cutaneous Manifestation Caused by Stenotrophomonas maltophilia in a Leukemic Patient - Son, Young Min (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
Ecthyma gangrenosum (EG) is a well-recognized cutaneous infection that most commonly affects immunocompromised patients. It typically occurs on the extremities, or in gluteal and perineal regions. Although Pseudomonas aeruginosa is the most well-known pathogen causing EG, other organisms have been reported to cause EG. Herein we report a rare case of ecthyma gangrenosum presenting as aggressive necrotic skin lesions in perioral and infraorbital areas in a 47-year-old patient with acute myelocytic leukemia after allogeneic bone marrow transplantation. It was caused by Stenotrophomonas maltophilia, which is an aerobic, gram-negative pathogen that has been associated only rarely with cutaneous disease. Blood culture and tissue culture were positive for S. maltophilia. Histological examination revealed numerous tiny bacilli in the dermis and perivascular area. Early recognition of skin lesions caused by S. maltophilia is important to decrease associated mortality in immunosuppressed patients.